Pengaruh Good Corporate Governance, Corporate Social Reposibility dan Rasio Likuiditas Terhadap Kinerja Keuangan (Studi pada Sub Sektor Food & Beverage di Bursa Efek Indonesia 2019-2023) - Alyaa Rihhadatul Aisy; Muhammad Zaini (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2024)
This study aims to analyze the influence of Good Corporate Governance, which is proxied through the board of directors (X1), audit committee (X2), and the proportion of independent commissioners (X3), as well as Corporate Social Responsibility (X4) and Liquidity Ratio measured by Current Ratio (X5), on Financial Performance proxied through Return on Asset (ROA) (Y) in Food & Beverage sector companies listed on the Indonesia Stock Exchange in 2019-2023. Through the purposive sampling method, a sample of 26 companies was obtained for 5 years. The analysis was carried out using Eviews version 13 software, with techniques including determining data regression models, classical assumption tests, multiple linear regressions, and hypothesis tests. The results of the study show that simultaneously, the board of directors, audit committee, proportion of independent commissioners, CSR, and current ratio have a significant effect on ROA. However, partial tests indicate that each of these variables does not have a significant influence on ROA individually. This model explains that independent variables affect ROA by 50%, while the remaining 50% is influenced by other variables that are not studied,